Islamic Educational Values in the Berume Tradition in Toweren Village, Lut Tawar District, Central Aceh Regency (1999–2026) - Erni Fitri; Birrul Walidaini; Ramadan R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The berume tradition is one of the local wisdom practices of the Gayo community in Toweren Village, Lut Tawar District, Central Aceh Regency, which embodies various Islamic educational values. However, modernization, social change, and the declining participation of younger generations have posed challenges to its preservation. This study aims to identify the Islamic educational values embedded in the berume tradition and analyze the obstacles in maintaining these values. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The informants consisted of village leaders, kejurun belang (traditional agricultural leaders), religious figures, and community members involved in the tradition. The findings reveal that the berume tradition contains Islamic educational values such as ukhuwah Islamiyah (Islamic brotherhood), ta’awun (mutual assistance), trustworthiness and responsibility, hard work, patience, sincerity, and gratitude. The obstacles identified include the declining interest of younger generations, reduced understanding of religious values, the weakening spirit of mutual cooperation, modernization, globalization, and economic pressures. Therefore, the berume tradition functions not only as an agricultural activity but also as a medium for Islamic education and character building that deserves to be preserved and sustained.